Efficacy of aerobic exercise for HIV-associated neurocognitive disorders receiving ART: An RCT - Martins Nweke; Nombeko Mshunqane (South African Journal of Physiotherapy)
Background: HIV-associated neurocognitive disorder (HAND) affects an individual’s capacity for independence and engagement in everyday activities, posing challenges in environments with limited resources and low social support.